Anthropometric profiles of Filipino badminton collegiate players - Kim, Mihyun (Asia Life Sciences : the Asian International Journal of Life Sciences, 2013)
The objective of this study was to analyze the anthropometric measurements of Filipino collegiate players. Fifty badminton collegiate players (Female n = 27, mean (SD) age 17.07 (1.35); Male n = 23, mean age 18.43 (2.00) years) were assessed on anthropometric variables: stature, body mass and skinfold thickness. Results showed that female players had lower BMI (Body Mass Index) and higher sum of skinfolds compared to males. Waist-to hip ratio (WHR) scores of males and females were similar, but WHR score of females was 0.83, which is a measure of abdominal adiposity. It is a concern that female players appear to have more fat than normally found in badminton players. Aside from additional aerobic workout in the female players' conditioning program, proper nutritional assistance is suggested.